Fragment Search in Acyclic Structures - Randic, Milan (Journal of chemical information and computer sciences, 1978)
A graph theoretical algorithm is described which allows a search for fragments in acyclic structures. Although the topic discussed in the paper is of limited immediate use, it provides a basis for atom-by-atom matching which may be practical as a large number of unproductive matchings are eliminated from consideration. The approach is based on the concept of atom codes which register the number of neighbors one, two, and more bonds apart. Atom codes provide a means of strong information on a structure (i.e. connectivity) without an explicit use of atom labels. Atom codes also permit assignment of multiple labels to individual vertices based on some specified rules or prescribed properties.